(3QSGdI CNhGf GdUaGA hNdGf GdhaGs - (3eLehYI eDdajf (B( (3ENhGf GdUaG(B)s ((3eHGQc Hf YHO Gddg GdYdGe ZdGe fLjH GdOjf GdeRjOi s)
(3ChdgG (B:s
(3GYde jG CNj Cf GdfGS eNJdahf ai CQGFge hePGgHe hUfGjYge s
(3BNQgG (B:s
(3hHbjJ ai GdHQRN Edi JeJ GdQSGdI GdNGeSI ef GdbSe GdQGHY s
(3GdeDda gh CHh SdjeGf eMeO Hf fUQ GdHSJi hCNQhfs
(3gPG GdeNWhW YHGQI Yf NeSI QSGFd gi GdChdi GdCQGA hGdOjGfGJ GdfHhjI hGdePGgH GdadSajIs
(3GdKGfi ai eGgjI GdWQjb Edi Gddg hcjajI GdhUhd Edjg s
(3GdKGdKI ai HjGf GYJbGO ENhGf GdUaG s
(3GdQGHYI ai HjGf c s
(3bQf GdfSN (B:s
Keywords: (3GdadSaI hGdefWbs